Integrating Gender into World Bank Financed Transport Programs : Component 1. Case Study Summary and Final Report - IC Net (World Bank, Washington, DC, 2014)
The World Bank in November 2001 commissioned IC Net Limited of Japan to carry out a study titled 'Integrating Gender into World Bank Financed Transport Programs' in accord with the terms of reference (TOR) issued in June 2001. The study was financed by a grant from the Japanese Large Studies Trust Fund. The contract came into effect on 15 December 2001 and covers the period to 15 June 2004. IC Net was to work in association with TRL Limited and the International Forum for Rural Transport and Development, both of the United Kingdom. The TOR defines the overall objective of the study as follows: 'to assist the World Bank and other international development agencies, developing country governments and Non-Governmental Organizations (NGOs), to improve the efficiency and equity of transport policies and programs through ensuring that projects respond to the needs of both women and men.' This report brings together the findings of ten case studies from nine countries (China, Laos, Vietnam, Bangladesh [two studies], Senegal, Lesotho, South Africa, Uganda and Peru) for component one. A common analytical framework for all the case studies was developed to: understand and examine transport projects in the framework of national gender policy, governmental resource allocation to gender activities and gendered social structure; and capture the gender characteristics of the households and individuals that projects were intended to impact upon. The case studies found a gap between the national gender framework and inclusion of gender in the transport sector. In other words, a gender-enabling environment, e.g. reference to gender in the constitution and gender focal points in many of the case study countries, did not necessarily result in concrete gender practice across the transport sector.